Exploitation Cinema and the Lesbian Imagination - Anne Crémieux (Transatlantica)
When they were first released, exploitation films were harshly criticized for their depiction of women and homosexuals. However, with the distance of time and the transformation of society, feminist audiences are reclaiming films whose quaint queers they can now enjoy not only as a trace of the past, but also as subversive characters they are seeing in a new light. This paper focuses on exploitation films such as Faster Pussycat! Kill! Kill! (1965) or Cleopatra Jones and the Casino of Gold (1975), and their reassessment, including in films and TV series that pay homage to female action heroines of the past.